Production of Pectinolytic Enzymes by the Yeast Wickerhanomyces anomalus Isolated from Citrus Fruits Peels - Martos, María Alicia (2013)
Wickerhamomyces anomalus is pectinolytic yeast isolated from citrus fruits peels in the province of Misiones, Argentine. In the present work, enzymes produced by this yeast strain were characterized, and polygalacturonase physicochemical properties were determined in order to evaluate the application of the supernatant in the maceration of potato tissues. W. anomalus was able to produce PGin liquid mediumcontaining glucose and citrus pectin,whosemode of actionwas mainly of endo type.The supernatant did not exhibit esterase or lyase activity. No others enzymes, capable of hydrolyzing cell wall polymers, such as cellulases and xylanases,were detected. PGshowedmaximal activity atpH4.5 and at temperature range between 40∘Cand50∘C. It was stable in the pH range from3.0 to 6.0 and up to 50∘Cat optimumpH.The enzymatic extractmacerated potato tissues efficiently.Volume of single cells increased with the agitation speed.The results observed make the enzymatic extract produced by W. anomalus appropriate for future application in food industry, mainly for the production of fruit nectars or mashed of vegetables such as potato or cassava, of regional interest in the province of Misiones, Argentine.